A History of the Four Georges, Volume II - McCarthy, Justin, 1830-1912 (Salt Lake City, UT : Project Gutenberg, 2007)
"A History of the Four Georges, Volume II" by Justin McCarthy is a historical account written in the late 19th century. The book provides a detailed exploration of the reigns of King George I, George II, and George III of Great Britain, focusing on the political intricacies, notable events, and cultural shifts of the period. The author delves into significant topics such as political controversies, royal family dynamics, and key figures, offering insights into both personal and national histories during this transformative era. The opening of the volume begins with a reflection on historical figures like Daniel Defoe and John Gay, noting their contributions to literature and politics as their lives conclude amid the complex political landscape of early 18th-century Britain. It examines the political dynamics of the time, including the rivalry between the government and the Patriots, highlighting significant debates in Parliament and the controversies surrounding government ministers like Walpole. Through this, McCarthy sets the stage for a broader discussion on the impact of these historical characters on contemporary British politics and society, as well as exploring underlying themes of power, ambition, and public sentiment during the reigns of the Four Georges. (This is an automatically generated summary.)
Release date is 2007-11-22
E-text prepared by Al Haines
Keywords: Great Britain -- History -- 1714-1837; Great Britain -- Politics and government -- 1714-1837